2007
DOI: 10.1080/00032710701585537
|View full text |Cite
|
Sign up to set email alerts
|

Sensing System Integrating Lanthanum Hydroxide Nanowires with Copper(II) Ion for Uracil and its Application

Abstract: A sensing system for uracil was constituted by using lanthanum hydroxide nanowires (LNW) as a modifier to obtain LNW modified carbon paste electrode (LNW/CPE) and by introducing copper(II) ion into supporting electrolyte to transform electroinactive uracil to electroactive uracil-Cu(II) complex. The voltammetric behaviors of uracil in the presence of Cu(II) ion at LNW/CPE were investigated. A reduction peak of the uracil-Cu(II) complex at 20.18 V was the two-electron reduction of Cu(II) ion in the uracil-Cu(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As for as solid-phase extraction method (Salvador et al, 2006) is concerned, Ura and 5FU were reportedly coeluted with other endogenous substances of plasma. Whereas HPLC/ UV (Maring et al, 2005;Deporte et al, 2006), HPLC/fluorescence (Yoshida et al, 1986;Kindberg et al, 1989), GC/MS (Shin et al, 1998;Mashiyama et al, 2008) and voltammetric methods (Mirceski et al, 2000;Liu et al, 2007) showed impressive Ura and 5FU sensitivity, integration with advanced technology such as LC/MS (Jiang et al, 2002;Salvador et al, 2006) required costly and sophisticated instrumentation. To the best of our knowledge, no work related to direct SPME for Ura and 5FU analysis in biological fluids has hitherto been reported barring a few SPME analyses of substituted Ura herbicides (Beltran et al, 2000;Krutz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As for as solid-phase extraction method (Salvador et al, 2006) is concerned, Ura and 5FU were reportedly coeluted with other endogenous substances of plasma. Whereas HPLC/ UV (Maring et al, 2005;Deporte et al, 2006), HPLC/fluorescence (Yoshida et al, 1986;Kindberg et al, 1989), GC/MS (Shin et al, 1998;Mashiyama et al, 2008) and voltammetric methods (Mirceski et al, 2000;Liu et al, 2007) showed impressive Ura and 5FU sensitivity, integration with advanced technology such as LC/MS (Jiang et al, 2002;Salvador et al, 2006) required costly and sophisticated instrumentation. To the best of our knowledge, no work related to direct SPME for Ura and 5FU analysis in biological fluids has hitherto been reported barring a few SPME analyses of substituted Ura herbicides (Beltran et al, 2000;Krutz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%